The Politics of Cycling Infrastructure : Spaces and (In)Equality - Koglin, Till; Cox, Peter (Book collections on Project MUSE., 2020)
This book offers a critical examination of existing cycling structures and the current policy and practices used to promote cycling in Europe. An international range of contributors provide an interdisciplinary analysis of the complex cultural politics of infrastructural provision and interrogate the pervasive bias against cyclists in city planning and transport systems across the globe.Infrastructural planning is revealed to be an intensely political act and its meaning variable according to larger political processes and contexts. The book also considers questions surrounding safety and risk, urban space wars and sustainable futures, connecting this to broader questions about citizenship and justice in contemporary cities. -- [4ème de couverture]